Implementation of Mentoring Programs in Order to Building Islamic Character: Case Study of Sriwijaya University Students - Arung Samudera; Muhammad Uyun (Tazkiya Journal of Psychology, 2022)
The phenomenon of a decline in moral quality in the younger generation is an issue that often arises in the last few decades, including students. So, we need a solution that is able to answer the challenges of these troubling problems. One solution that can be offered is to hold a mentoring program for them.This study aims to identify the impact of the mentoring program in the process of forming Islamic character in Sriwijaya University students. The subjects used in this study were muslim students of who were active in the mentoring program with an age range of 18-23 years. This study uses a descriptive approach with data collection methods, interviews, observations, and discussions. This study shows that students experience changes in behavior and the formation of Islamic character. For students who are diligent in participating in mentoring programs on regularly. The islamic characters that are formed are the characters of iman, taqwa, respect and courtesy, caring, patience, humility (tawadhu), trust and also honesty.